Correlation of Concentration Ethyl Acetate Fraction of Calabash Fruit (Crescentia cujete L.) with Mortality Haemonchus contortus Worm In Vitro - Dyah Ajeng Suhita; Anwar Ma'ruf; Agus Sunarso; Eduardus Bimo Aksono Herupradoto; Dewa Ketut Meles (Journal of Parasite Science)
The purpose of this study was to ascertain how the concentration of the ethyl acetate component of calabash fruit (Crescentia cujete L.) affected the in vitro mortality of the Haemonchus contortus worm. This study employed a post-test only control group design as its methodology. There were five treatments, with a total of four repetitions. Twenty H. contortus worms were utilized as samples in each treatment throughout all replications. Observation and recording of H. contortus mortality was carried out at 5, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60 minutes, and when all worms in the petri dish died. Worm mortality was observed by examining whether there was a movement reaction from the worms when given a touch or water droplets at 50°C. Linear regression test was used to assess the data. The resulting linear equation, y = 2.417 + 5.875x, demonstrated that the ethyl acetate component of calabash fruit had an impact on worm mortality. The conclusion of this study is that the increase in the concentration of the ethyl acetate fraction is directly proportional to the mortality of the worm Haemonchus contortus in vitro with an effect value of 93.4%.